2016
DOI: 10.1177/0271678x15625352
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the cerebral cortex in sporadic small vessel disease: A systematic review of in vivo MRI data

Abstract: Cerebral small vessel diseases of the brain are a major determinant of cognitive impairment in the elderly. In small vessel diseases, the most easily identifiable lesions, both at post-mortem evaluation and magnetic resonance imaging, lie in subcortical areas. However, recent results obtained post-mortem, particularly in severe cases, have highlighted the burden of cortex lesions such as microinfarcts and diffuse neuronal loss. The recent development of image post-processing methods allows now assessing in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
(241 reference statements)
0
23
0
Order By: Relevance
“…Neurodegeneration (diffuse cortical and subcortical grey matter atrophy, parieto‐temporal glucose hypometabolism) is another finding reported in sporadic CSVD . DPA‐ as well as CAA‐related neurodegeneration seems thereby to be quite widespread (in frontal, temporal, occipital, insular, hippocampal regions) . One latest study additionally reported an association between greater progressive posterior white matter connectivity loss and greater progression of occipital cortical thinning .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 90%
See 1 more Smart Citation
“…Neurodegeneration (diffuse cortical and subcortical grey matter atrophy, parieto‐temporal glucose hypometabolism) is another finding reported in sporadic CSVD . DPA‐ as well as CAA‐related neurodegeneration seems thereby to be quite widespread (in frontal, temporal, occipital, insular, hippocampal regions) . One latest study additionally reported an association between greater progressive posterior white matter connectivity loss and greater progression of occipital cortical thinning .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 90%
“…One latest study additionally reported an association between greater progressive posterior white matter connectivity loss and greater progression of occipital cortical thinning . Indeed, results on CSVD neurodegeneration patterns are inhomogeneous, demanding for the disentanglement of the additional impact of concomitant neurodegenerative disorders as a concurrent source of cortical alterations .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 92%
“…Regional atrophy of pyramidal cells without other characteristics of neurodegenerative disease has been described and associated with clinical dementia, and it has been proposed that the underlying cause is vascular . In addition, imaging studies have indicated a correlation between cortical thinning and WMD but have been criticized for not taking the possible co‐occurrence of neurodegenerative disease into account .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies identified MRI markers of SVD (lacunes, white matter hyperintensities, cerebral microbleeds, silent infarcts, white matter changes, global cerebral atrophy, medial-temporal lobe atrophy) as determinants of VaD (18,19). Vascular lesions traditionally attributed to VCI comprise subcortical areas of the brain, especially subfrontal white matter circuits, strategic areas of single infarction such as the dominant thalamus or angular gyrus, deep frontal areas and the left hemisphere, and bilateral brain infarcts or volume-driven cortical-subcortical infarctions reaching a critical threshold of tissue loss or injury (20). Recently, enlargements of perivascular spaces were identified as MRI markers of SVD.…”
Section: Imaging Morphologic Substrates Of Svdmentioning
confidence: 99%